Digital trailblazer essential lessons to jumpstart transformation and accelerate your technology leadership - Sacolick, Isaac (Hoboken Wiley, 2022)
In Digital Trailblazer: Essential Lessons to Jumpstart Transformation and Accelerate Your Technology Leadership, Isaac Sacolick, a technology leadership expert and a former CIO and CTO, delivers a hands-on guide to help technology and business professionals at all stages of their careers acquire the skills necessary to drive transformative change. With an eye-opening collection of stories and more than 50 lessons, Sacolick gives readers a view into what goes on behind-the-scenes in leading digital transformations. From tense IT Ops conference calls to make-or-break executive meetings, Sacolick presents the challenging scenarios faced by product, technology, and data leaders and helps readers learn to lead transformations and become Digital Trailblazers.
Includes index.
Keywords: Leadership